Expectations and service quality: perceived performance at low-season events. Issue 2 (10th May 2019) - Meleddu, Marta; Melis, Giuseppe; Pulina, Manuela; Zapata-Aguirre, Sandra
Abstract : Purpose: Events play a strategic role to attract tourist flows especially during the low season. The purpose of this paper is to explore the gap between consumers' expectations and actual satisfaction at cultural events. Design/methodology/approach: A principal components analysis identifies a set of orthogonal factors related to visitors' expectations and actual satisfaction at two different events. The empirical data were collected during two events. The geographical setting is Sardinia (Italy) where two important cultural events are held in the low season: the Cavalcata (held at the end of May) and the Sartiglia (held during Carnival). A representative random sample is collected taking into account gender, age and visitors' nationality heterogeneity (Italian, English-speakers, French and Spanish). Findings: Some homogeneous findings have been obtained for the two events, regardless of the different levels of attractiveness. Notably, both the events are perceived as authentic and as the expression of identity. On the whole, the empirical results indicate that the events were able to generate high levels of satisfaction. Research limitations/implications: The main limitation of this research is that the data refer to only one year, while a wider time series could allow a more accurate evaluation of both the expectations and the performance results deriving from the management of the two events. The findings provide directions to local policy makers to adopt tailored strategies to boost strengths and to contrast weaknesses of low season events. Practical implications: The methodological approach presented in this paper helps practitioners and policy makers to deepen their understanding of visitors' actual experience as well as to improve the overall quantity and quality of services offered during the events. Social implications: An in-depth analysis of the perceived quality of the services provided at events can allow public and private organizers to identify critical issues, enabling them to improve event planning, efficiency, profitability and overall performance. Originality/value: This paper employs an "Importance-Performance" model (Martilla and James, 1977; Riviezzo et al., 2009 ) to study the gap between visitors' expectations and their perceived performance in two events held during the low tourist season. Thanks to the use of an equivalent survey, the comparison offered the opportunity to highlight common features that allowed a generalization of results and a broader discussion.